KEKUATAN HUKUM ALAT BANTU PENDETEKSI MATA SEBAGAI ALAT PEMBUKTIAN - Muhammad Wahyudi; Hari Soeskandi (Gapenas Publisher, 2023)
As time goes on, the use of eye detection tools has become more widespread, both in the workplace and in the legal process in Indonesia. While these tools are a relatively new technology in Indonesia and have both benefits and drawbacks that must be considered, their importance in collecting relevant and reliable evidence in court cannot be denied. The use of eye detection tools can facilitate the investigation process and provide a higher level of legal certainty for those involved. However, there are still issues that need to be addressed regarding the use of eye detection tools as evidence in legal proceedings, such as the lack of regulation in Indonesian law. Therefore, it is important to have a deeper understanding of the legal status of eye detection tools in the criminal judicial process in Indonesia. The goal of this research is to examine the legal strength of eye detection tools as a support tool in the criminal judicial process in Indonesia. The research method used is normative juridical, involving an analysis of relevant laws and journals. In this research, there are issues that need to be addressed, including the lack of regulation on the legal status of eye detection tools as evidence in criminal proceedings and the lack of regulation in Law No. 8 of 1981 on the Criminal Procedure Code. Despite this, eye detection tools are widely used in various places, such as hospitals, offices, and others. The public sees the existence of eye detection tools as providing certainty and security in terms of data protection.